Inspiratory muscle training: a simple cost-effective treatment for inspiratory stridor. Issue 10 (4th May 2007) - Dickinson, John; Whyte, Greg; McConnell, Alison
Abstract : This case study describes the support given to a British elite athlete in the build up to the 2004 Athens Olympic Games. The athlete had complained of breathing symptoms during high intensity training that led to a reduction in performance and premature cessation of training. Following a negative eucapnic voluntary hyperpnoea challenge and observation during high intensity exercise, the athlete was diagnosed with inspiratory stridor. Inspiratory muscle training (IMT) was implemented to attenuate the inspiratory stridor. Following an 11-week IMT programme, the athlete had a 31% increase in mouth inspiratory pressure and a reduction in recovery between high intensity sprints. The athlete reported a precipitous fall in symptoms and was able to complete high intensity training without symptoms. This case shows that IMT is a suitable cost-effective intervention for athletes who present with inspiratory stridor.